Coherent structure generated in the boundary layer of a laboratory‐created ionospheric depletion. Issue 5 (13th March 2014) - Liu, Yu; Cao, Jinxiang; Xu, Liang; Zhang, Xiao; Wang, Pi; Wang, Jian; Du, Yinchang; Zheng, Zhe
<x xml:space="preserve">Abstract</x> Laboratory experiments have been conducted to simulate the boundary processes of ionospheric depletion. The ionospheric depletion was modeled through releasing depletion chemical (SF6) into the ambient plasmas. These plasmas were segregated into two regions by a boundary layer of width electric scale length. In the localized boundary layer, the electron density decreased sharply that yielded steep density gradients. Meanwhile, the floating potential increased in the time scales of the lower hybrid (LH) period, which produced strong sheared electron flows. The shear frequency ωs=VE/LE, which characterizes the sheared flow, is much larger than the LH frequency ωLH. A coherent structure was observed when the floating potential fluctuations were analyzed using digital spectral analysis techniques. Comparison with the theory indicated that the structure is driven by the electron‐ion hybrid instability which is generated owing to the nonlinear coupling between the electron density gradient and the sheared electron flow. Our results are important to study the early phase nonlinear evolution of the ionospheric depletion, especially in the development of plasma irregularities and turbulence in the boundary layer.